O rozwoju polskich dialektów - Wyderka, Bogusław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
The article deals with a phenomenon of the evolution of dialects. With respect to traditional dialects, the new post-dialectal formations are characterized not so much by the systemic changes but rather by the functional and pragmatic ones; thus, in their defining, those phenomena should be considered. The first change that had occurred in the original phase of the creation of the Polish ethnical language, under the influence of the dominating variation (i.e., culturally supreme), was the change of the hierarchies of inflexion in the diasystem of the national language, from a horizontal organization (equivalent dialects) into hierarchical one (dominating literary language and functionally limited, socially influenced folk dialects). The fundamental alterations occurred as late as the second half of the 20th century. The first communication breakthrough took place after World War II as a result of migrations of people and civilizational transformations. This brought about changes that were called linguistic integration. There formed interdialects – nowadays, the forms dominating in Polish rural areas. The second communication breakthrough began in 1990s and was a result of changes of the systems of government, globalization and rapid civilizational advances. At that time, there occurred the development of dialects which went beyond their defined framework. In Polish linguistic area there form post-dialectal formations of regiolects of Kurpie, Podhale and Silesia, which systemically stem from dialects. Such phenomena can be termed as the emancipation of dialects. They are the expression of a modern regional identity being under construction.